2021
DOI: 10.1007/s00701-021-04720-7
|View full text |Cite
|
Sign up to set email alerts
|

New-onset seizures after cranioplasty—a different view on a putatively frequently observed phenomenon

Abstract: Background New-onset seizures after cranioplasty (NOSAC) are reported to be a frequent complication of cranioplasty (CP) after decompressive hemicraniectomy (DHC). There are considerable differences in the incidence of NOSAC and contradictory data about presumed risk factors in the literature. We suggest NOSAC to be a consequence of patients’ initial condition which led to DHC, rather than a complication of subsequent CP. We conducted a retrospective analysis to verify our hypothesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, interestingly, all patients had their seizures within 24 hours post CP. Which, contrary to Hirschmann et al's argument [ 46 ], suggests that the CP procedure itself may play some role in provoking seizures even in some indirect way, and not entirely caused by the initial disease. Moreover, in contrast to several studies where new onset seizures were found in patients with THI, hemorrhagic or ischemic strokes, our study noted that the surgical site osteomyelitis infection on the previous craniotomy site was the indication for craniectomy in two patients, and the tumor was the indication in the third.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…However, interestingly, all patients had their seizures within 24 hours post CP. Which, contrary to Hirschmann et al's argument [ 46 ], suggests that the CP procedure itself may play some role in provoking seizures even in some indirect way, and not entirely caused by the initial disease. Moreover, in contrast to several studies where new onset seizures were found in patients with THI, hemorrhagic or ischemic strokes, our study noted that the surgical site osteomyelitis infection on the previous craniotomy site was the indication for craniectomy in two patients, and the tumor was the indication in the third.…”
Section: Discussionmentioning
confidence: 64%
“…New onset seizure is another frequently reported complication post CP, with an incidence rate between 2.7% to 30.3% [ 45 ]. Several risk factors have been identified as contributory to its incidence including the time interval between craniectomy and CP, patient age at CP, presence of VP shunt at time of CP, type of material used, the indication for the craniectomy, hypertension (HTN), and diabetes mellitus (DM) [ 46 ]. However, these risk factors once again are inconsistent in the literature, and some even are contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations